Helen Keller International's Enhanced-Homestead Food Production Program in Burkina Faso (EHFP) - Olney, Deanna K.; Dillon, Andrew (International Food Policy Research Institute, 2010)
Helen Keller International (HKI) has been implementing homestead food production (HFP) programs in Asia for the past 20 years and has recently begun implementing HFP programs in Africa as well. In general, these programs target women and are designed to improve maternal and child health and nutrition outcomes. The start date is February 2010 and estimated completion date is June 2017. The collaborators for this trial are: United States Agency for International Development (USAID); Bill and Melinda Gates Foundation. The International Food Policy Research Institute (IFPRI) sponsored this trial.